Componentes de produção, produtividade, adaptabilidade e estabilidade fenotípica de materiais de soja no Paraná - Oliveira, Giovani Andreazza de (2018)
Due to the high investment required and the high phenotypic variability of soybean cultivars, experimental trials with the aim of identifying the genotypes with agronomic performance more responsive to different environments became essential in order to reduce the chances of obtaining poor results, which may make the activity unfeasible. Thus, this study was developed with the objective of evaluating the production components, the adaptability and phenotypic stability of soybean genotypes in Paraná. For this, experiments were conducted in the environments of Campo Mourão, Itaipulândia and Palotina - PR during the 2016/17 season. The experimental design consisted of randomized blocks, composed of 30 genotypes, in three replications, totaling 90 plots per environment. The variables evaluated were: plant height at maturity (APM), number of days for maturation (NDM), number of legumen per plant (NLPP), number of grains per plant (NGPP) and grain yield. The methodologies proposed by Eberhart and Russell and Lin and Binns were used to determine the adaptability and phenotypic stability of productivity. For the APM characteristic only the genotypes L.E.01 and M 5892 IPRO could lead to losses during the mechanized harvest when cultivated in Campo Mourão. The genotypes BMX ELITE RSF IPRO, DM 54I52 RSF IPRO and L.E.01, are among the earliest genotypes, and their cycle is classified as precocious or semi-precocious depending on the environment. NDM ranged from 101.7 to 127 days, 110 to 113.7 days and 80.7 to 140 days for Campo Mourão, Itaipulândia and Palotina respectively. Regarding the NLPP and NGPP characteristics for Campo Mourão, the material M 5892 IPRO consisted of the worst material for both characteristics. In Itaipulândia the variation corresponded between 29.5 to 61 legumen plant-1 and 83.1 to 181.9 plant-1 grains, being the genotypes classified in two groupings. In Pallotina the genotypes that presented the lowest NLPP also showed the lowest NGPP. Campo Mourão was the environment that presented the lowest average for grain yield, while in Palotina the best results were obtained. For the Pearson correlations, the NDM production component contributed the most to grain yield. The material L.E.01 always integrated the cluster with the lowest production averages in all environments evaluated. Based on the methodology proposed by Eberhart and Russel (1966), it was verified that 13 cultivars presented adaptability to favorable environments (ß1> 1) and 16 to unfavorable environments (ß1 <1), with only L.E.03 and NS 5445 showed R2 less than 80%. All evaluated genotypes showed significant regression deviation, that is, low phenotypic stability (S²d> 0). The methodology of Lin and Binns (1988) classified the BMX GARRA RSF IPRO genotypes, L.E. 02 and L.E. 04 as high stability and adapted to unfavorable environments, while the BMX genotypes TORNADO RSF IPRO, M 5947 IPRO and DM 61I59 RSF IPRO being low stability and adapted to favorable environments.